The Importance of Transformational Leadership in Creating Work Engagement to Improve Employee Performance: A Case Study of a Private University in Jakarta - Yuli Evitha, (Technium Social Sciences Journal, 2024)
This study aims at answering the questions how the work engagement of employees is in each department, what strategy is employed to improve employee performance and what type of leadership is expected by the staff. This study employed a case study approach of a qualitative research design. In this study a semi- structured interview is used to understand how participants experienced the phenomenon. The results of this study prove that work engagement will not be owned by every employee if it is not led by a transformational leader who can provide motivation and guidance to his subordinates and make the work atmosphere comfortable, so that his subordinates will feel they have a sense of belonging, towards the organization. This research also proves that transformational leaders always trust their staff and encourage them to be creative and innovative. Thus the performance of employees will increase and the organization will be more advanced with its human resource assets. This study provides insight into a view to improve the employee performance through work engagement and the role of transformational leadership and offers recommendations for future research.